2007
DOI: 10.1371/journal.pone.0000798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transferrin Receptor and the ABC Transporters ABCB6 and ABCB7 for Resistance and Differentiation of Tumor Cells towards Artesunate

Abstract: The anti-malarial artesunate also exerts profound anti-cancer activity. The susceptibility of tumor cells to artesunate can be enhanced by ferrous iron. The transferrin receptor (TfR) is involved in iron uptake by internalization of transferrin and is over-expressed in rapidly growing tumors. The ATP-binding cassette (ABC) transporters ABCB6 and ABCB7 are also involved in iron homeostasis. To investigate whether these proteins play a role for sensitivity towards artesunate, Oncotest's 36 cell line panel was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 40 publications
4
63
0
1
Order By: Relevance
“…19 Like ABCB6, ABCC13 affects clinical response to neoadjuvant chemotherapy in breast cancer. 37 In the present study their expressions were strongly correlated.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…19 Like ABCB6, ABCC13 affects clinical response to neoadjuvant chemotherapy in breast cancer. 37 In the present study their expressions were strongly correlated.…”
supporting
confidence: 66%
“…36 Otherwise, ABCB6 was shown to be involved in resistance of tumor cells towards artesunate 37 and to be significantly overexpressed in melanoma cells, when compared to normal melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In antitumor approaches, for example, numerous constructs have been reported that target transferrin receptor, [39][40][41][42][43][44][45] since this receptor has been reported to be expressed at levels approximately twofold higher in tumors than in normal tissues. 46,47 Intuitively, a twofold difference may not provide a sufficient differential between tumor and normal tissue to confer tumor selectivity, unless the dose-response curve of the therapeutic entity is very steep.…”
mentioning
confidence: 99%
“…ABCB6 is a member of the B (MDR/TAP) subfamily of ABC transporters best known as drug-resistance genes, and it can form homodimers [19]. Indeed, increased ABCB6 expression correlates with increased drug resistance in multiple cell lines [34,35]. A specific ABCB6 function was first described in Saccharomyces cerevisiae mutants lacking mitochondrial ABC transporter Atm1p [36].…”
Section: Discussionmentioning
confidence: 99%